HUBUNGAN LINGKUNGAN SOSIAL DENGAN PERILAKU ROKOK ELERITRIK VAPE PADA SISWA SMK SASMITA JAYA PAMULANG TAHUN 2024 - Oktavianus Ngedo Bulu; Weslei Daeli; Indri Sarwili (JOURNAL SAINS STUDENT RESEARCH, 2024)
Background : Background: Based on data from the Indonesian Ministry of Health ini 2018, the prevalence of e-smokers in the city of Palembang was 16.2%. %. This number could increase significantly due to the increasingly rapid development of e- cigarettes, which can cause impacts and health problems for teenagers. Therefore, this research aims to determine the social environment of e-smoking behavior among teenagers in the city of Tenggerng Pamulang so that effective prevention efforts can be made. Research objective: To understand the relationship between the social environment and the use of e-cigarettes in Class 10 at SMK Sasmita Jaya Pamulang in 2024. Method: The research used in this research is a descriptive correlation research design with a cross sectional approach. Correlation design is research that connects one variable with another, and a cross sectional approach. The population in this study were 10th grade teenagers at Sasmita Jaya Pamulangn Vocational School with a total of 74 respondents. The technique used was Probability Sampling Technique, Stratified Random Sampling Technique, Data Analysis Using the Chi Square Test with. Results: the statistical test obtained a value (p-value = 0. 9.987) so it was concluded that there was no relationship between the social environment and the use of e-cigarette vapes in class 10 students at Sasmita Jaya Pamulang Vocational School. Conclusion: there is no relationship between the social environment and the use of e-cigarette vapes among students in class 10 at SMK Sasmita Jaya Pamulang